Exploring carbon sequestration potential through 3D concrete printing - Tay, Daniel Yi Wei (2024)
As global CO2 concentrations rise, there is a pressing need for sustainable alternatives in the construction sector as many countries are striving to attain net carbon neutrality. Integrating carbon capture and sequestration (CCS) technologies directly into 3D concrete printing offer a promising solution to reduce the carbon footprint in the construction sector. This paper investigates a novel printing technique involving the purging of pressurised CO2 gas was demonstrated and the various process parameters were evaluated for its effectiveness in promoting carbon sequestration. Results show that the carbon-sequestrated sample has a 15% increase in carbon uptake as compared to the control sample. The method can be complementary to existing sequestration technologies, facilitating large-scale carbon sequestration without chamber size limitations. Nevertheless, further research and development are necessary to optimise the various printing parameters and achieve a more balanced and efficient integration of carbon capture and sequestration technologies with 3DCP.